The Role of Management Information Systems in the Decision-Making Process in the Hospital Sector - Kasih Puji Utami, NurWening, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Management Information System (MIS)is an information which in addition to performing all necessary transaction processing for an organization. Hospitals are organizations where healthcare professionals provide complex care using specialized knowledge and equipment to meet patients’ care needs. Conventionally, hospitals comprise different clinical departments and functional units. However, there have not been many studies that have reviewed other research studies on how useful management information systems are in the health care sector in the hospital sector.This paper is a literature review that discusses management information systems in decision making, especially in the field of hospital health services. Articles are collected by Google, Google Scholars and medeley databases. The review is carried out on articles with the topic of management information systems or decisionmaking systems, especially those related to the hospital sector. We identified about 20 articles published in the last decade then analysed and drew conclusions.The results of this study indicate that the implementation of management information systems in the field of health services, especially hospitals, is known to be able to have several impacts, such aspatient satisfaction, strengthen internal communication network, reduce costs store data reliably in a digital environment, store data reliably in a digital environment, improve service quality, assist managers in decision making, fast data collection, and speed up and simplify financial reports.